Kepribadian Tokoh Utama dalam Novel Yuni Karya Ade Ubaidil Kajian Psikologi Sastra - Wahyuningtyas, Dinda; ., Sukardi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
This study aims to examine the personality of the main character in describing the personality of the main character. The novel in this research is Ade Ubaidil's Yuni Novel which was adapted from Kamila Andini's Yuni film. The method used is descriptive qualitative with a description of the contents, the focus used for this research is in the literature review. The data collection technique used is the reading and note technique. The results of these studies are as follows. The personality of the main character in Sigmund Freud's theory has 3 types of personality, namely id, ego, and superego. Yuni's figure in the id aspect is seen in the personality of psychic energy or instinct that has been carried from birth, this aspect always seeks pleasure and avoids things that are uncomfortable. On the ego aspect, Yuni feels spiritual roles such as: problem solving, decision making and reasoning. And the aspect of Yuni's superego shows the good and bad values ​​of decisions taken such as secretly taking money from Mrs. Ndek's cupboard).